Development of Video-Based Learning Materials for the English Syntax Course for English Education Students at IAIN Metro - Puspito, Toto Andri (Tarbawiyah Jurnal Ilmiah Pendidikan, 2023)
This article draft adapts a research proposal into the Tarbawiyah journal format. The study is designed to develop video-based learning media for the English Syntax course for students of the English Education Department at IAIN Metro and to examine its feasibility for classroom use. The rationale of the study lies in the digital transformation of higher education and in the abstract, sequential, and repetitive nature of syntax materials, which require students to revisit explanations several times. The study employs a Research and Development design adapted from Sugiyono, covering needs analysis, product design, expert validation, revision, limited try-out, and final revision. Data are planned to be collected through questionnaires, interviews, observation sheets, and learning tests. The expected product is an instructional video that is clear, attractive, repeatable, and suitable for independent learning. In the full empirical version of the article, the results section should report expert-validation scores, student responses, and learning outcomes.